Efektivitas Absensi Elektronik Dalam Meningkatkan Disiplin Kerja Pegawai Di Dinas Komunikasi Dan Informatika Kota Banjar - Tika Aprianti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
Entitled "Effectiveness of Electronic Attendance in Improving Employee Work Discipline in the Office of Communication and Information Technology in Banjar City". With the development of increasingly sophisticated technology, the government has created an electronic (online) attendance system in government agencies that aims to improve employee work discipline. The purpose of this study is to find out how the effectiveness and impact is given from the implementation of electronic (online) attendance on employee work discipline. This study used a qualitative descriptive study, where the data collection techniques were through observation, interviews and documentation. The results of the study show that the application of online attendance at the Office of Communication and Information in the City of Banjar has gone quite well. The object of this research is the Office of Communication and Informatics of the City of Banjar. Electronic attendance (online) is an attendance system that is carried out online from an employee's device. This device will then be connected to the office database system, so that when an employee processes attendance, it will be recorded directly. There has been an increase in employee work discipline with the implementation of electronic (online) attendance but it is not yet effective enough because there are still problems in its use. This shows that there are changes that are quite influential for employees to comply with regulations in accordance with the rules that have been set.